Analysis of Students' Mathematical Communication Skills in Project-Based Learning - Khaerani, Khaerani; Rahmawati, Rahmawati; Syamsuriyawati, Syamsuriyawati; Kamaruddin, Rahmat; Mamara, Nuraeni Handang (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Mathematical communication ability is an essential 21st century skill that needs to be possessed by mathematics education students. However, initial studies show that students often experience difficulties in conveying mathematical ideas in writing and visually, which is partly due to the use of conventional learning models that do not support interaction and exploration. This study aims to analyze students' mathematical communication skills in the context of project- based learning, as well as to identify the forms of mathematical communication that emerge and the factors that influence them. This research used descriptive qualitative approach with case study method. The subjects consisted of 9 students of Mathematics Education Study Program of Maros Muslim University who were selected purposively. Data were collected through participatory observation, in-depth interviews, and project documentation, then analyzed through the stages of reduction, presentation, and conclusion drawing. The results showed that students' oral communication and visual representation developed significantly through group discussions and project presentations. However, aspects of written communication were still weak, especially in the use of logical structure and consistency of mathematical symbols. The implication of this finding indicates the need to strengthen the written communication aspect through the integration of mathematical writing exercises in the curriculum, as well as the provision of learning spaces that support students' courage in communicating reflectively and structurally